Banjir: Fakta dan Dampaknya, Serta Pengaruh dari Perubahan Guna Lahan - Arief Rosyidie (Journal of Regional and City Planning, 2013)
Water is a resource that plays an important role in supporting the human activities and human. Until now, its function and role for human beings cannot be replaced by other resources. However, the excess of water at the wrong time and place can cause a range of problems for our life and livelihood as well as the decline in the quality of the environment. For years and until recently, floods has not only experienced by developing countries, such as in Indonesia, but also by developed countries. Floods can be caused by many factors, which are grouped into natural and human factors, but this problem is mainly caused by human activities which do not take the carrying capacity of the environment and the variability of climatic condition into consideration. Contribution of each factor to flooding in different areas will be different, one of the important factors related to urban and regional planning is the change in land use. The impact of flooding on the environment, economy, and social are also varied among one region to another. This paper discusses the phenomenon of flooding, causes, impacts, and mitigation with illustration case on flooding in some areas, especially areas of Bandung.Keywords: water resources, disaster, flood areas, land use.